Essential Oil of Thymus munbyanus subsp. coloratus from Algeria: Chemotypification and in vitro Biological Activities. Issue 3 (16th February 2017) - Bendif, Hamdi; Boudjeniba, Messaoud; Miara, Mohamed Djamel; Biqiku, Loreta; Bramucci, Massimo; Lupidi, Giulio; Quassinti, Luana; Vitali, Luca A.; Maggi, Filippo
Abstract : Thymus munbyanus subsp. coloratus (Lamiaceae) is a small shrub endemic to Algeria and Morocco where is found in lawns, rockeries and mountainous regions. From a phytochemical point of view this taxon has never been characterized. In this work we have analysed the chemical compositions of the essential oils obtained from inflorescences and vegetative parts by GC/MS. A new chemotype, i.e . borneol‐chemotype, was characterized for the first time in the species. Furthermore, we assessed the biological activities of essential oils, namely the antioxidant, antimicrobial and cytotoxicity on tumor cells that were evaluated by the DPPH, ABTS, and FRAP, disc diffusion, and MTT methods, respectively. Biological assays highlighted a moderate inhibitory effect on Staphylococcus aureus, Escherichia coli and Candida albicans (inhibition zone diameter in the range 9 – 10 mm), and noteworthy cytotoxicity on A375 human melanoma cells ( IC 50 of 46.95 μg/ml). Abstract :